2011
DOI: 10.1074/mcp.m111.007765
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Glycopeptides Associated with Herceptin Treatment of Human Breast Carcinoma MCF-7 and T-Lymphoblastoid Cells

Abstract: The therapeutic humanized monoclonal antibody IgG1 known as Herceptin ® has shown remarkable antitumor effects. Although this type of therapy has increased the cancer-free survival of patients, not all tumors respond to this treatment and cancers often develop resistance to the antibody. Despite the fact that Herceptin function has been extensively studied, the precise mechanism underlying its antitumor activity still remains incompletely defined. We previously demonstrated on human breast MCF-7 carcinoma and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
9
0
1
Order By: Relevance
“…Previously, we have found several proteins (PrP(C), p75(NTR), GAS1 and RhoE) that play important roles in MDR of gastric cancer, which unfortunately, are not sufficient enough to elucidate the development of MDR [11][12][13][14]. Recently, the correlation between drug resistance and change of glycoproteins has been reported in several papers [9,10,32,33]. But currently, there is no report concerning the relation between alteration of glycoproteins and MDR in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have found several proteins (PrP(C), p75(NTR), GAS1 and RhoE) that play important roles in MDR of gastric cancer, which unfortunately, are not sufficient enough to elucidate the development of MDR [11][12][13][14]. Recently, the correlation between drug resistance and change of glycoproteins has been reported in several papers [9,10,32,33]. But currently, there is no report concerning the relation between alteration of glycoproteins and MDR in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Di Michele et al screened the differential expressed glycoproteins between drug sensitive and resistant cell lines and found 4 glycoproteins remarkably upregulated in drug resistant cells as putative biomarkers for paclitaxel resistance in ovarian cancer [9]. Another study reported that treatment with molecule targeted drug herceptin could lead to dramatic differences of glycoproteins in breast cancer and T-lymphoblastoid cells [10]. But unfortunately, until now there is no study focusing on the correlation between the changes of glycoproteins and MDR in gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, recent researches indicated that glycomic alterations of glycoproteins exerted enormous effects on chemoresistance of cancers. Lattova et al verified the correlations between N-glycosylation variations and the efficacy of chemotherapies in breast cancer cells [ 23 , 24 ] and discovered that the emergence of galactosylated or biantennary fucosylated glycans might be associated with chemoresistance. Besides, Nakano et al observed that α 2–6 sialylation of N-glycans decreased with acquired resistance to desoxyepothilone B in leukemia cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phenylhydrazine (PHN) labelling was applied to enhance ionization of the glycans in the positive mode. 51 From Fig. 8A, it is observed that relative abundance ratios of neutral species remained unchanged (versus Fig.…”
Section: Characterization Of Free Glycansmentioning
confidence: 90%